The Oxford handbook of law and economics. Volume 1, Methodology and concepts - Parisi, Francesco, 1962- (Oxford : Oxford University Press, 2017)
The Oxford Handbook of Law and Economics covers over one-hundred topics on issues ranging from law and neuroeconomics to European Union law and economics to feminist theory and law and economics. The book gathers together scholars and experts in law and economics to create the most inclusive and current work on law and economics. Volume 1 surveys methodology and concepts.
The Future of Law and Economics / Gary S. Becker, Richard A. Posner -- Economic Models of Law / Thomas J. Miceli -- Empirical Law and Economics / Jonathan Klick -- Bounded Rationality, Behavioral Economics, and the Law / Christine Jolls -- Experimental Economics and the Law / Charles Holt, Sean P. Sullivan -- Experimental Psychology and the Law / Tess Wilkinson-Ryan -- Social Psychology and the Law / Pam Mueller, Janice Nadler -- Evolutionary Law and Economics / Georg von Wangenheim -- Public Choice Theory and Legal Institutions / Daniel A. Farber -- Constitutional Economics and the Law / Stefan Voigt -- Law, Economics and Positive Political Theory / Emerson H. Tiller -- Contractarian Perspectives in Law and Economics / Georg Vanberg, Viktor Vanberg -- Austrian Perspectives in Law and Economics / Shruti Rajagopalan, Mario J. Rizzo -- Moral Philosophy and Law and Economics / Brian H. Bix -- Critiques of Law and Economics / David Driesen, Robin Paul Malloy -- Income Redistribution Through the Law / Chris William Sanchirico -- Cost-Benefit Analysis in Legal Decision-Making / Richard O. Zerbe Jr. -- Well-Being and Public Policy / John Bronsteen, Christopher Buccafusco, Jonathan Masur -- Value-Driven Behavior and the Law / Tom R. Tyler -- Law and Social Norms / Emanuela Carbonara -- Mechanism Design and the Law / t
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Law and economics